Effectiveness of mat Pilates on postural alignment in the sagittal plane in school children: a randomized clinical trial - Fabíola Unbehaun Cibinello; Jessica Caroliny de Jesus Neves; Mônica Yosino Leão Carvalho; Paola Janeiro Valenciano; Dirce Shizuko Fujisawa (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: This study aimed to investigate the effectiveness of the mat Pilates method, an exercise program, on postural alignment in the sagittal plane among children aged between 8 and 12 years. Method: This study used a blind randomized controlled clinical trial, with a Pilates group (PG) and control group (CG) at the Early Childhood Education Institute. A total of 40 children were randomized, who have no prior knowledge of the Pilates method and no exercise training in the last six months. Mat Pilates exercises were administered twice a week for four months in 50-minute sessions. Postural alignment in the sagittal plane was assessed using photogrammetry. Results: There was no statistically significant difference between the groups post-intervention A significant difference was found in the following outcomes that represent an improvement in intragroup postural alignment: among the children in PG, in the right sagittal view in the vertical body alignment (p=0.019; effect size, ES = 0.70; standardize response mean, SRM = 0.57) and in the sagittal head angle (p=0.035; ES = 0.41; SRM = 0.51). Among the children in the CG, in the vertical alignment of the trunk in the left sagittal view (p= 0.016; ES = 0.50; SRM = 0.44). Conclusion: The effectiveness of Pilates on postural alignment in the sagittal plane among children aged between 8 and 12 years was not confirmed.